2020
DOI: 10.1038/s41598-020-59642-8
|View full text |Cite
|
Sign up to set email alerts
|

Multiple time-scale beats in aurora: precise orchestration via magnetospheric chorus waves

Abstract: the brightness of aurorae in earth's polar region often beats with periods ranging from sub-second to a few tens of a second. past observations showed that the beat of the aurora is composed of a superposition of two independent periodicities that co-exist hierarchically. However, the origin of such multiple time-scale beats in aurora remains poorly understood due to a lack of measurements with sufficiently high temporal resolution. By coordinating experiments using ultrafast auroral imagers deployed in the Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(63 citation statements)
references
References 40 publications
6
57
0
Order By: Relevance
“…This comparison again demonstrates an exact one‐to‐one correspondence between these two periodic phenomena, which has already been reported by Hosokawa, Miyoshi, et al. (2020).…”
Section: Observationssupporting
confidence: 88%
See 1 more Smart Citation
“…This comparison again demonstrates an exact one‐to‐one correspondence between these two periodic phenomena, which has already been reported by Hosokawa, Miyoshi, et al. (2020).…”
Section: Observationssupporting
confidence: 88%
“…Later, Hosokawa, Miyoshi, et al. (2020) employed the wave data from Arase to show the complete one‐to‐one correspondence between the temporal variations of PsA and LBC. In particular, they identified two sets of good correspondence: (1) Between the main pulsation and chorus bursts, and (2) between the internal modulation and chorus elements, as predicted by Miyoshi, Saito, et al.…”
Section: Introductionmentioning
confidence: 99%
“…These waves can be both a source and a loss mechanism for radiation belt particles (Horne & Thorne, 1998; Meredith et al, 2003; Miyoshi et al, 2003; Reeves et al, 2013; Thorne et al, 2013; Turner et al, 2012). They are also believed to be responsible for diffuse and pulsating aurora (Agapitov et al, 2018; Hosokawa et al, 2020; Kasahara, Miyoshi, et al, 2018; Miyoshi, Saito, et al, 2015; Nishimura et al, 2010; Ozaki et al, 2019; Thorne et al, 2010), and possibly for plasmaspheric hiss as well (Bortnik et al, 2008, 2009; Meredith et al, 2013; Santolik et al, 2006), although there are alternative theories (e.g., Falkowski et al, 2017). Additional studies and current open research questions related to chorus waves can be found in Ripoll et al (2020) and references therein.…”
Section: Introduction/backgroundmentioning
confidence: 99%
“…These observational results imply that PsA is the two-dimensional projection of the characteristics of chorus waves in the magnetosphere. Although recent literatures, which analyzed the simultaneous groundsatellite observations, have revealed the correspondence between PsA and chorus waves (e.g., Kasahara et al 2018;Hosokawa et al 2020), it is still unclear what factors control these periodic variations.…”
Section: Open Accessmentioning
confidence: 99%